Is a Mexican Pine Species Better Adapted to the Warming Climate of the Southwestern USA? - Hess, Victoria A.; Fulé, Peter Z. (Frontiers in Forests and Global Change, 2020)
Pinus leiophylla, or Chihuahua pine, (PILE) and P. ponderosa, or ponderosa pine, (PIPO) are two wide-ranging North American species with distributions that overlap in Arizona, USA. We compared the growth of fifty-eight trees from three study sites over an elevation gradient at the northernmost point of PILE occurrence. Because the PILE trees were growing at the extreme edge of the species´ range, we expected that PILE sensitivity to climate would be higher and growth performance would be reduced compared to PIPO. From 1918 to 2017, the study area became drier and warmer with precipitation declining by approximately 9% while temperature rose by approximately 5%. We found that PILE tree-ring indices were more sensitive in terms of average year-to-year percent variation than those of PIPO and had higher variability in tree-ring variation in the ten wettest vs. the ten driest years. But PILE displayed higher absolute diameter growth rates as measured by basal area index (BAI) and was less negatively correlated with warm monthly temperatures. Within species, low-elevation trees of both species tended to have greater sensitivity to climate over all variables assessed, but the differences were not statistically significant. The overall assessment of growth of paired trees of the two species showed the locally rare species PILE to perform approximately equally as well as the dominant species PIPO. Species migration is reshaping global forests but species found predominantly in Mexico with distributions coinciding closely with national boundaries have received insufficient research attention in the USA. We recommend cross-border, climate-focused, comprehensive studies on PILE and other species likely to migrate northward to provide critical information for conservation and management of forest resources.